Student-Teachers’ Perception of the Preparedness to Engage in Online Teaching, and Challenges They Face When Teaching Online: A Corpus Analysis of Their Reflexive Journal Entries - Hazidi Abdul Hamid; Md Rosli Ismail; Abdul Aziz Md. Nor; Rosinah Mahmood; Eti Fairudz Zainudin (2021)
The Covid19 pandemic changed the way almost everything is done, including teaching. Online teaching rose to become the quintessential way mode of teaching in weeks after being in relative obscurity the two decades of its existence. Online teaching is now prominent, but research shows that we are still lacking knowledge in almost every human aspect involved in online teaching. This study focusses on student-teachers’ perceptions of their own preparedness to teach online and the challenges they face when teaching online. This is done by looking into the primary keywords or concepts the student-teachers use in their own writing. Language is our ubiquitous tool by which we look into the minds of fellow human beings. Accordingly, this study looks at a body of language (corpus) compiled from the reflective journals produced by 23 student-teachers as part of their final assessment portfolio (+700 pages, +800,000 words). These journals embody their thoughts during their practical teaching experience. The analysis is carried out using a concordancer program. By analysing this corpus, we will, (1) identify the most prominently occurring content words, and (2) the most prominently occurring words relative to the prominent keywords. The resulting semantic web will display the concepts the preoccupy the concerns of these respondents thus giving us an insight into possible areas that we need to focus on in our efforts to remedy and enhance our online teaching capabilities. Initial findings show that the most prominent word in their writing ‘students’ with technical and technology concerns falling far behind.